2015
DOI: 10.1051/0004-6361/201425268
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry in disks

Abstract: Aims. We study the deuteration and ionization structure of the DM Tau disk via interferometric observations and modelling of the key molecular ions, HCO + and DCO + . Methods. The Plateau de Bure Array is used to observe DM Tau in lines of HCO + (1−0), (3−2) and DCO + (3−2) with a ∼1.5 angular and ∼0.2 km s −1 spectral resolution. Using a power-law fitting approach the observed column densities profiles are derived and thus the isotopic ratio R D = DCO + /HCO + . Chemical modelling allowed an exploration of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 103 publications
(134 reference statements)
7
81
1
Order By: Relevance
“…Ring-like distributions have previously been inferred for DCO + in the TW Hya, HD 163296, and DM Tau disks Mathews et al 2013;Teague et al 2015), and ring-like emission patterns are observed for AS 209, V4046 Sgr, MWC 480, and HD 163296 in this work. These results suggest that ring-like DCO + distributions are common, and support a cold H 2 D + formation scenario.…”
supporting
confidence: 75%
“…Ring-like distributions have previously been inferred for DCO + in the TW Hya, HD 163296, and DM Tau disks Mathews et al 2013;Teague et al 2015), and ring-like emission patterns are observed for AS 209, V4046 Sgr, MWC 480, and HD 163296 in this work. These results suggest that ring-like DCO + distributions are common, and support a cold H 2 D + formation scenario.…”
supporting
confidence: 75%
“…However, decreasing the UV excess by only a factor of 10 relative to the fiducial model results in an increase in J = 4−3 flux of only 9%. The UV radiation efficiently ionizes atomic metals, and the resulting electrons efficiently destroy HCO + (Teague et al 2015). The increase in flux is not so dramatic for longer wavelength lines.…”
Section: Hco + Chemistrymentioning
confidence: 99%
“…As a result of the small sizes and demanding integration times, spatially resolved line observations of protoplanetary disks are still relatively rare and the radial distributions of molecules are poorly constrained (see Piétu et al 2007;Chapillon et al 2012b;Qi et al 2013a;Teague et al 2015). Also, until a few years ago, large telescopes or interferometers had limited bandwidth, so a full spectral survey required substantial observing time, often of order 100 of hours or more, as only a few lines could be observed simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Also, until a few years ago, large telescopes or interferometers had limited bandwidth, so a full spectral survey required substantial observing time, often of order 100 of hours or more, as only a few lines could be observed simultaneously. Nonetheless, limited spatially resolved molecular surveys targeting a handful of sources in lines of several simple species were performed by the Chemistry in Disks (CID; Dutrey et al 2007Dutrey et al , 2011Schreyer et al 2008;Henning et al 2010;Chapillon et al 2012b;Teague et al 2015) and Disk Imaging Survey of Chemistry with SMA (DISCS; Öberg et al 2010, 2011) consortia.…”
Section: Introductionmentioning
confidence: 99%